How to teach mathematics - Krantz, Steven George, 1951- (Providence, R.I. : American Mathematical Society, 1999)
This expanded edition of the original bestseller, How to Teach Mathematics, offers hands-on guidance for teaching mathematics in the modern classroom setting. Twelve appendices have been added that are written by experts who have a wide range of opinions and viewpoints on the major teaching issues. Eschewing generalities, the award-winning author and teacher, Steven Krantz, addresses issues such as preparation, presentation, discipline, and grading. He also emphasizes specifics--from how to deal with students who beg for extra points on an exam to mastering blackboard technique to how to use applications effectively. No other contemporary book addresses the principles of good teaching in such a comprehensive and cogent manner. The broad appeal of this text makes it accessible to areas other than mathematics. The principles presented can apply to a variety of disciplines--from music to English to business. Lively and humorous, yet serious and sensible, this volume offers readers incisive information and practical applications.
Table of Contents •Guiding principles •Practical matters •Spiritual matters •Difficult matters •A new beginning •Appendices •The irrelevance of calculus reform: Ruminations of a sage-on-the-stage •Mathematical content •Personal thoughts on mature teaching •Remember the students •Reflections on Krantz's How to Teach Mathematics: A different view •Are we encouraging our students to think mathematically? •Big business, race, and gender in mathematics reform •Will this be on the exam? •Teaching or appearing to teach: What's the difference? •Why (and how) I teach without long lectures •The joy of lecturing--with a critique of the romantic tradition in education writing •Teaching freshmen to learn mathematics •Bibliography •Index
Includes bibliographical references (p. 285-290) and index.
Keywords: Mathematics -- Study and teaching; Wiskunde -- Didactiek